PSO-Optimized CoVID-19 MLP-NARX mortality prediction model - Ihsan, Mohd Yassin; Azlee, Zabidi; Megat Syahirul Amin, Ali; Rahimi, Baharom (Institute of Electrical and Electronics Engineers Inc., 2021)
Mortality prediction models localized for Malaysia is limited, warranting a research gap to study further. A predictive model for CoVID-19 mortality prediction is presented in this paper. The model utilized the MLP-NARX structure. Parameters for the model were optimized using PSO. Prediction results yielded average MSE value of 8.1141× 10× {-7} with acceptable validation results.